Edinost v Kristusu, izhajajoč iz Kratke pripovedi o antikristu Vladimirja Solovjova - Žust, Milan (Edinost in dialog, 2014)
What really unites us Christians and what can reunite us? We believe that we can grow in unity, if in the power of the Holy Spirit we became members of the same body of Christ and in Him sons and daughters of the same Father. Interesting, challenging and always actual image of this unity in Jesus Christ is A Short Story of the Anti-Christ of Vladimir Soloviev, which can be the starting point for the reflection about the fundaments of ecumenical dialogue and about some actual issues in the relations among Catholics and Orthodox. Although the theological dialogue is very important to overcome the schism of several centuries, it should be first of all well prepared and then supported with creation of suitable atmosphere. Here are of fundamental importance the interpersonal relations, which in addition to the mutual knowledge and acquaintance include also the readiness to pardon and to acknowledge one's own mistakes and those in the history of ones own Church. All this is possible only in strong personal relation with Jesus Christ, taking part in His Easter mystery.
Keywords: Solov'ev, Vladimir Sergeevič, 1853-1900; kristologija; ecumenism; ekumenizem; ruska književnost; Russian literature; literarna interpretacija